A Feasibility Study on The Enforcement of Good Manufacturing Practice (GMP) for Surgical Gloves - ลากุล กิตติมา; ฉลองสุข ระพีพรรณ (Journal of Health Science of Thailand, 2024)
This study was aimed to find an enforcement feasibility of the revised Good Manufacturing Practice (GMP) version for surgical gloves by studying the operational capabilities of government officials and workers from surgical glove manufacturers in accordance with requirements of the GMP, and studying the readiness of government authorities, manufacturers, and importers of surgical gloves to be complied with the GMP enforcement, as well as studying the potential impact of the GMP enforcement for surgical glove manufacturers and importers. The revised GMP version was analyzed for enforcement readiness with 4 factors (4M). Also, an impact was analyzed with 4 factors (4P). Data were collected by interviewing 13 government officials, 7 workers from surgical glove manufacturers and and 3 workers from importers. The analysis was performed with content analysis by grouping of data and applying descriptive statistics. The findings revealed that government officials and surgical glove manufacturers in Thailand were able to follow and operate with the requirements and procedures of the revised GMP version but were not ready to regulate due to the lack of knowledge, understanding and manpower. The building infrastructure needed to be improved, including purchasing various equipment in order to cover the new requirements, especially the surgical glove importers which had to coordinate with international manufacturers for the GMP quality system. In conclusion, the enforcement of GMP would have a negative impact on costs and expenses, such as increasing of the cost of auditors, equipment costs, building infrastructure costs and other related costs. However, if the International Organization for Standardization (ISO 13485) is accepted and surgical glove manufacturers have certified with the ISO 13485 standard, it will be deemed to be certified the GMP standard. Alternative approach is to take a specific audit on topics which are different from the ISO 13485 standard. This would reduce the burden and expenses for both government officials, and surgical glove manufacturers and importers.